2012
DOI: 10.1126/science.1220845
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Period for Social Experience–Dependent Oligodendrocyte Maturation and Myelination

Abstract: A Critical Period for Glia The brain develops in fits and starts—while one system is completed, another system may still be under construction. Such transient states are known as critical periods, and during these specific aspects of brain development may become more sensitive to outside agents than they would be later. Makinodan et al. (p. 1357 ) observed the effect of environmental conditions on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

39
790
6
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 790 publications
(885 citation statements)
references
References 38 publications
39
790
6
2
Order By: Relevance
“…These dramatic developments in neural structure and function may be affected by the social environment available at or before this developmental stage (Makinodan et al 2012;Sheridan et al 2012). A multitude of studies have established that social isolation and loneliness are a significant determinant of physical health and longevity (Cacioppo and Hawkley 2009;Holt-Lunstad et al 2010;Uchino et al 1996), and mental health in humans (see Hawkley and Cacioppo 2010;Heinrich and Gullone 2006, for reviews).…”
Section: Behavioral and Cortical Development In Adolescencementioning
confidence: 99%
See 1 more Smart Citation
“…These dramatic developments in neural structure and function may be affected by the social environment available at or before this developmental stage (Makinodan et al 2012;Sheridan et al 2012). A multitude of studies have established that social isolation and loneliness are a significant determinant of physical health and longevity (Cacioppo and Hawkley 2009;Holt-Lunstad et al 2010;Uchino et al 1996), and mental health in humans (see Hawkley and Cacioppo 2010;Heinrich and Gullone 2006, for reviews).…”
Section: Behavioral and Cortical Development In Adolescencementioning
confidence: 99%
“…Individuals that perceive themselves as isolated and lonely show weaker prefrontal and ventral striatal reward system responses to pleasant pictures of people, less activation in perspective-taking areas of temporo-parietal cortex , and more maladaptive cardiovascular responses to threatening or negative stimuli (Ong et al 2012). Research has also shown that children who experience isolation early in development show significantly smaller gray matter and white matter volumes as adolescents (Mehta et al 2009), and that isolation in post-weaned animals reduces myelination of white matter tracts (Makinodan et al 2012) and reduces prefrontal cortical volume (Fone and Porkess 2008). Although these studies of isolation do not perfectly mirror the An additional factor to consider, when examining links between social experiences and neural patterns, is that individual differences in the relative dominance of one hemisphere over the other have been linked to certain psychological styles (Tomarken et al 1992).…”
Section: Behavioral and Cortical Development In Adolescencementioning
confidence: 99%
“…The membrane-bound neuregulin1 (NRG1) is an axonal ligand for glial ErbB receptors, and NRG1-ErbB signaling is required for myelination in both the peripheral and central nervous systems [5][6][7][8]. To examine whether this signaling pathway has a role in the early-stage myelin pruning, we first used two previously characterized morpholino oligomers (MOs) to knock down the expression of NRG1 in zebrafish larvae.…”
Section: Dear Editormentioning
confidence: 99%
“…Las investigaciones en neurociencias y particularmente los estudios por neuro-imágenes demuestran que la mielinización y desarrollo de las neuronas dependen, desde el principio de la vida, de la calidad y cantidad de estímulos que el niño reciba en su interacción con su entorno. Este proceso se vería comprometido por la experiencia de aislamiento social y de carencia afectiva a muy temprana edad 27 . Esta condición traumática se encuentra asociada a un déficit en la mielinización que podría modificar la velocidad de conducción de los impulsos y dificultar un mejor procesamiento de la información, pudiendo además relacionarse con déficits en la memoria y en las interacciones sociales 28 .…”
Section: La Carencia Afectiva Y Sus Implicanciasunclassified